Analysis of students critical thinking skills using essay tests on topics of rate reaction - Tiania Riziella Yusar; Desy Kurniawati (Jurnal Pijar Mipa, 2023)
The study aims to describe the percentage of students' critical thinking skills in senior high school of grade ten SMAN 1 Payakumbuh in reaction rate topic. The type of research is descriptive quantitative, with a sample were 72 students. Samples were taken in random sampling. The instrument used was an essay test that included indicators of Ennis' critical thinking skills. The results showed that students critical thinking skills, with the highest percentage of 87.22%, were found in deciding an action. The lowest percentage was 4.81%, namely in the indicator of observing and considering observation reports. The total percentage of students' critical thinking skills in the reaction rate material, equal to 60.39%, is included in the low category.